Slovenski narod - Logar, Nataša (Teorija in praksa, 2018)
In the article, we explore inter-sentence inserts (parentheses) as a textconstruction technique. A sample of 253 examples of inter-sentence inserts, and a further 121 sentence-independent inserts were collected from 30 issues of the newspaper Slovenski narod published in 1873, 1893, 1913 and 1933. Syntactic and orthographic analyses were performed, along with analysis of the content. Our study revealed the dominant use of exposure inter-sentence inserts (in contrast to a smaller number of by-inserts). Approximately half the exposure inter-sentence inserts were marked with a comma. Content-wise, almost three-quarters of the inter-sentence inserts in the sample were metadiscoursal. The study confirmed that inter-sentence inserts were indeed an important part of the beginnings of the news reporting genre in Slovenia.
Keywords: medstava; metabesedilnost; parenteza; skladnja; Slovenian newspapers; Slovenski časniki; Slovenski narod (periodična publikacija); Stilistika; Stylistics; vrinjeni stavek